A multi-omics study of magnesium sulfate to improve prognosis in sepsis-related encephalopathy: integrating clinical data-driven network pharmacology - Kong, Yingming; Tai, Yanghao; Chen, Bin; Zhang, Meng; Ji, Haoyu; Feng, Rongke; Shi, Liang; Chen, Hao (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSepsis-associated encephalopathy (SAE) constitutes a significant neurological manifestation of sepsis, characterized by high mortality rates and posing a critical threat to patient outcomes. Magnesium sulfate has multiple effects in the nervous system, including neuroprotection, sedation, anticonvulsant activity, enhanced neuroplasticity, anti - inflammation and promotion of nerve repair. It can regulate calcium homeostasis, exert antioxidant effects, and reduce the release of inflammatory factors, thereby alleviating neuronal damage and neurological deficits. This study integrated MIMIC-IV database and network pharmacology to explore magnesium sulfate’s neuroprotective mechanisms and clinical impact on SAE outcomes.MethodsRetrospective data from 4,650 SAE patients in MIMIC-IV 3.0 were analyzed. Propensity score matching balanced covariates. Cox models and Kaplan-Meier curves evaluated magnesium sulfate’s association with 28-day all-cause mortality (ACM). Network pharmacology identified magnesium sulfate’s core targets and pathways.Results4183 patients (89.96%) received magnesium sulfate during ICU, while 467 (10.04%) did not receive. The 28-day ACM in patients with SAE was 11.05%. After propensity score matching participants with and without magnesium sulfate administration had 28-day ACM of 17.29% and 30.42%, respectively (P < 0.001). Magnesium sulfate administration was associated with reduced 28-day ACM. Subgroup analysis revealed this association differed in several stratification. Network pharmacology revealed magnesium sulfate targets TNF, IL6, IL1B and CXCL8, modulating pathways including inflammatory response, immune regulation, and cellular stress.ConclusionsMagnesium sulfate use correlates with improved SAE survival, particularly those with comorbid chronic obstructive pulmonary disease and acute kidney injury, and using vasoconstrictors, likely through multi-target modulation of inflammatory response and immune regulation. Prospective studies are needed for validation.